Relasi budaya arab dengan agama islam terhadap penyebaran ajaran islam - Amanulloh, Rara Nailalmuna; Ghozi, Ahmad; Gunardi, Muhammad Fawwaz Putra; Ullah, Alia Asad (Maliki Interdisciplinary Journal, 2025)
This study examines the close relationship between Arab culture and Islamic teachings as the primary foundation for the spread and development of Islamic civilization across the globe. Islam, born in the Arabian Peninsula, brought with it local cultural values ​​that subsequently transformed and interacted with other cultures as the religion spread. This study employed a qualitative research method with a literature study approach, focusing on the analysis of various scientific sources related to the history, culture, and dynamics of the spread of Islam. The results show that Arab culture played a significant role in strengthening the character and identity of Islamic teachings, particularly through Arabic as a medium of da'wah (Islamic propagation), literary traditions such as poetry and verse, and art and architecture imbued with Islamic values. Furthermore, the heyday of the Abbasid and Umayyad dynasties marked a significant milestone in the spread of Islamic knowledge, philosophy, and culture to various parts of the world, including Europe, Africa, and Southeast Asia. The acculturation between Arab and local cultures in these regions gave birth to diverse forms of Islamic civilization, yet still rooted in the principles of monotheism and the universal values ​​of Islam. Thus, the relationship between Arab culture and Islamic teachings not only shapes global Islamic identity, but also enriches the cultural and intellectual treasures of Muslims to this day.